Obstáculos a efetividade do laudo arbitral final do CIRCI - Centro Internacional para a Resolução de Controvérsias sobre Investimentos do Banco Mundial : as imunidades estatais - Soares, Mario Cezar Pedrosa (2008)
The study about the effectiveness of the final award uttered in the ambit ICSID – International Centre for the Settlement of Investment Disputes of the World Bank is current because a great flow of private foreign investment exists in activities that used to be monopolies of States. On the one hand, by means of privatizations, the public entity granted the private sector a chance to exploit and invest in areas that were exclusive of the State. On the other hand, the State plays an important role, acting as a regulator in this process. Usually, there is a long-term relationship between the recipient State and the foreign investor because the investors, at the outset, need to disburse a great amount of resources; and most often, the expected profits will not come in so fast. Many times the contracts between the State and the foreign investor are easily modifiable in favor of the States, either by political or market reasons. Governments still breach what they previously accorded, using its sovereignty and eminent domain power to expropriate private property, or to cancel concessions without just compensation. Nevertheless, it is necessary the implementation of reliable mechanisms for the pacification of such relationships representing the legitimate interests of both the State and the foreign investor. Additionally, in order to achieve a better result, it is mandatory that any regulatory institute be independent, impartial, not subject to outside influence, fast, and effective. Therefore, the present work will study the following topics: 1) the evolution of the foreign investments, analyzing the protection and promotion treaties; 2) the Bilateral Investment Treaties (BITs) of and the respective contractual issues; 3) the parties involved in this process; and 4) the procedures of the ICSID In sum, the major objective here is to assess how effective is the decision rendered in arbitration against sovereign states coupled with their governmental immunity system and the mechanisms adopted by the ICSID.